Knowledge, attitude and practice on postpartum haemorrhage among women in Kuantan, Pahang, Malaysia - Syed Idrus, Sharifah Nadiah; Jamani, Norjasmine Aida; Abdul Ghani, Radiah (Pharmascope.org, 2019)
Postpartum haemorrhage (PPH) is defined as excessive bleeding of 500 ml or more within 24 hours after birth. It is known as one of the leading cause of maternal mortality worldwide. In Malaysia, from the year 2009 to 2014, PPH remained as one of the top contributors to maternal deaths; this suggests that the knowledge, attitude and practice on PPH among mothers in Malaysia still need to be improved. This cross-sectional study is aimed to determine the level of knowledge, attitude and practice on PPH, in addition to examining the association of socio-demographic factors with knowledge, attitude and practice of women in Kuantan, Pahang, Malaysia. This study involved 105 women who have experienced pregnancy and delivered at least once and is living in Kuantan. Self-administered questionnaires were distributed from February until March 2018. Data were analysed using the Statistical Package Software for Social Sciences (SPSS). From the findings, the level of knowledge on PPH among women in Kuantan was average (n=73, 69.5%), whereas the level of attitude and practice of most respondents was found in a good level, 101 (96.2%) and 98 (93.3%) respectively. The factors that have significant associations with knowledge on PPH in this study were age group (p=0.016)and background of education (p<0.001). In conclusion, this study showed that most of the participants in Kuantan have a moderate level of knowledge on PPH yet possess a good attitude and practice on the management of PPH.